PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LK) PENDIDIKAN PANCASILA KELAS IV DALAM KURIKULUM MERDEKA DI SDN 01 PADANG LAWEH - Wiwik Okta Susilawati; Sonia Yulia Friska; Dwi Okta Pratiwi; Ahmad Ilham Asmaryadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to develop electronic worksheets for students of Pancasila education class IV, in order to add teaching materials in schools and produce electronic student worksheets (e-LK) for class IV Pancasila education that are valid, practical, and effective so as to improve results. learning students at SDN 01 Padang Laweh. This electronic student worksheet (e-LK) is assisted by live worksheets to make e-LK interesting. The development model used is the ADDIE model, namely analysis, design, development, implementation, and evaluation. Based on the results of validation by five validators, namely graphic, content, language, questions, and teaching module validators, an average score of 89% was obtained in the very valid category, practical results by class IV teacher practitioners and students obtained a percentage of 96.45%. with the very practical category, while the results of the effectiveness test in the form of test questions obtained a complete average of 89.47% with a very effective category.